Prolonged time to extubation after general anaesthesia is associated with early escalation of care: A retrospective observational study. Issue 5 (May 2021) - Vannucci, Andrea; Riordan, Isabella Rossi; Prifti, Kevin; Sebastiani, Anne; Helsten, Daniel L.; Lander, Daniel P.; Kallogjeri, Dorina; Cavallone, Laura
Abstract : BACKGROUND: Prolonged time to extubation after general anaesthesia has been defined as a time from the end of surgery to airway extubation of at least 15 min. This occurrence can result in ineffective utilisation of operating rooms and delays in patient care. It is unknown if unanticipated delayed extubation is associated with escalation of care. OBJECTIVES: To assess the frequency of 'prolonged extubation' after general anaesthesia and its association with 'escalation of care before discharge from the postanaesthesia care unit', defined as administration of reversal agents for opioids and benzodiazepines, airway re-intubation and need for ventilatory support. In addition, we tried to identify independent factors associated with 'prolonged extubation'. DESIGN: Single-centre retrospective study of cases performed from 1 January 2010 to 31 December 2014. SETTING: A large US tertiary academic medical centre. PATIENTS: Adult general anaesthesia cases excluding cardiothoracic, otolaryngology and neurosurgery procedures, classified as: Group 1 – regular extubation (⩽15 min); Group 2 – prolonged extubation (≥16 and ⩽60 min); Group 3 – very prolonged extubation (≥61 min). MAIN OUTCOME MEASURES: First, cases with prolonged time to extubation; second, instances of escalation of care per extubation group; third, independent factors associated with prolonged time to extubation. RESULTS: A total of 86 123 cases were analysed. Prolonged extubation occurred in 8138 cases (9.5%) and very prolonged extubation in 357 cases (0.4%). In Groups 1, 2 and 3 respectively, naloxone was used in 0.4, 4.1 and 3.9% of cases, flumazenil in 0.03, 0.6 and 2% and respiratory support in 0.2, 0.7 and 2%, and immediate re-intubation occurred in 0.1, 0.3 and 2.8% of cases. Several patient-related, anaesthesia-related and procedure-related factors were independently associated with prolonged time to extubation. CONCLUSION: Prolonged time to extubation occurred in nearly 10% of cases and was associated with an increased incidence of escalation of care. Many independent factors associated with 'prolonged extubation' were nonmodifiable by anaesthetic management. Abstract : Supplemental Digital Content is available in the text